Cultural Incompatibility in Digital News Adoption: Social Inequality and Political Information Dissemination in Indonesia - Nuzul Fadhli Ramadhan (MD Research Center, 2025)
This study focuses on how digital technology and culture mutually influence each other in shaping patterns of political participation in contemporary society. It is grounded in the reality that changes in the political landscape today are determined not only by developments in information technology but also by how local culture responds to and shapes the use of such technology. Using a qualitative approach through literature review, this research examines the dynamics of information technology development especially digital media in transforming political behavior and highlights the crucial role of cultural values and social norms in this process. The literature analyzed includes topics related to digital activism, the role of social media in political movements, and the responses of different social groups to technology adoption. The findings indicate that digital media has great potential to expand political participation space. However, this impact is not universal; it heavily depends on the surrounding social and cultural contexts. While technology enables more open and rapid political communication, factors such as digital access disparities and cultural diversity may limit the effectiveness of such participation. This study enriches the understanding of the interaction between digital media and local culture in political contexts and provides insight into how technology acts not just as a tool but also as a space shaped by and shaping the political cultural meanings of contemporary society.